Schedule of Activities and Program (Symphony in the Flint Hills, 2012)
2012 Schedule of activities, program notes, a biographical information about conductor Steven Jarvi, and information about the Kansas City Symphony.
Keywords: schedule; program notes; Kansas City Symphony; Steven Jarvi; Aundi Marie Moore